Use of electronic information resources among the Croatian scientists in the field of social sciences in a pre-digital library environment: obstacles and opportunities - Vrana, Radovan (2004)
While there are many research studies on research of user needs and requirements for use of information resources in electronic environment published in top research journals, there isn't almost any such research study published in Croatia, especially about the use of information resources in electronic environment by scientists in the field of social sciences. At the present moment, in Croatia, there still isn't any functional digital library. This situation, however, doesn't prevent scientist from using ever growing number of bibliographic and full text databases, available on the Internet. Since there are no quantitative data about scientists' preferences towards the use of printed or electronic resources, collaboration on scientific projects supported by information technology, advantages of electronic information resources in comparison with printed resources, obstacles they encounter during information retrieval sessions, it is necessary to collect data about enumerated and other issues concerning scientists' expectations about the usability of electronic information resources in general and digital libraries in particular. Purpose of this paper is to contribute to the debate on research on prerequisites for use of digital libraries by exploring user requirements and obstacles they encounter while using existing electronic information resources in a pre-digital environment. The paper will discuss competencies of special user categories such as scientists for use of electronic information resources for research and education while preparing for use of digital libraries in Croatia.
Projekt MZOS
ENG